CaMKII Phosphorylation in Primary Somatosensory Cortical Neurons is Involved in the Inhibition of Remifentanil-induced Hyperalgesia by Lidocaine in Male Sprague-Dawley Rats. Issue 1 (January 2016) - Cui, Weihua; Wang, Shanshan; Han, Ruquan; Wang, Qiang; Li, Junfa
Abstract : Background: Previous clinical studies have shown that lidocaine can alleviate severe postoperative pain after remifentanil-based anesthesia. Experimental studies have also demonstrated that lidocaine can inhibit remifentanil-induced hyperalgesia, yet the mechanism remains unknown. The present study explored the role of the primary somatosensory (S1) cortex in remifentanil-induced hyperalgesia as well as its inhibition by lidocaine through evaluation of Ca 2+ /calmodulin-dependent protein kinase II (CaMKII) phosphorylation and protein expression levels in S1 cortical neurons. Materials and Methods: Male Sprague-Dawley rats were randomly allocated to the following 3 groups: remifentanil only (R), lidocaine only (L), and remifentanil+lidocaine (RL). Experimentally naive animals were used as controls for immunoblotting and immunofluorescence evaluations. Via intravenous tail vein administration (24 G catheter), the animals received remifentanil at 2.4 μg/kg/min, lidocaine at 200 μg/kg/min, and remifentanil at 2.4 μg/kg/min plus lidocaine at 200 μg/kg/min for 2 hours. Paw withdrawal threshold (PWT) values for both mechanical and thermal hyperalgesia, along with immunoblotting and immunofluorescence, were used to measure remifentanil-induced hyperalgesia and changes in CaMKII phosphorylation (P-CaMKII) and total protein expression (T-CaMKII). Results: There was a significant decrease in the PWT for mechanical stimulation at 0.5 and 2 hours after discontinuing infusion in groups R and RL ( P <0.05, n=10 per group). However, there were no differences in thermal PWT in any group at any time period when compared with that of baseline. There was also a significant increase of P-CaMKII (not T-CaMKII) in S1 cortical neurons of group R (not L and RL groups) at 0 to 2 hours after discontinuing infusion when compared with that of the corresponding control group ( P <0.05, n=6 per group) as determined by immunoblotting and immunofluorescence microscopy. Conclusions: These results suggested that the phosphorylation of CaMKII in S1 cortical neurons increases significantly during the process of remifentanil-induced hyperalgesia. The increase of CaMKII phosphorylation could be inhibited by systemic application of lidocaine. This inhibition may play a role in the antihyperalgesia effects of lidocaine.